An Unusual Case of Left-Sided Poland Syndrome Presenting with Diaphragmatic Hernia and Mediastinal Shift with Absence of Hand and Scapular Deformity - S Venkatesh Kumar; M Vivekkumar; V Sanoj; K R Radhik; Sanjay Singh Rawat; Rohini Venkatesh (Journal of Orthopaedic Case Reports)
Introduction: Poland syndrome (PS) is a rare congenital condition often defined by unilateral aplasia of the pectoralis major, predominantly affecting the right side of the body. The second most prevalent manifestation is symbrachydactyly, characterized by excessively short and webbed fingers. Case Report: This report concerns an 18-year-old guy who presented to the orthopedic outpatient clinic with a complaint of left chest pain during exertion, identified with the rare left-sided PS characterized by the absence of the left antero-inferior pectoralis major muscle. The physical examination of the hands revealed no evidence of ipsilateral digital anomalies, a typical characteristic of PS. A significant characteristic is the concurrent presence of a little diaphragmatic hernia and a rightward shift of the mediastinum, frequently disregarded in standard presentations of PS; however, they affect the syndrome’s variability and intensity. The consanguinity of the patient’s parents necessitates an examination of possible genetic ramifications in an illness generally considered sporadic. Conclusion: This case presents a rare left-sided PS with diaphragmatic hernia and mediastinal shift but without hand or scapular abnormalities. The atypical presentation underscores the need for high clinical suspicion and detailed evaluation. While typically sporadic, consanguineous parentage suggests a possible genetic link.